Juridical Review of the Transfer of Mortgage Rights Without Creditor Consent from the Perspective of the Principles of Balance and Good Faith - Sitompul, Rosa Benedicta; Silalahi, Jur Udin (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study is motivated by the practice of transferring mortgage objects without the consent of creditors, which has the potential to create legal issues, particularly regarding the protection of creditors and third parties. Purposes of the Research: The purpose of this study is to analyze the legal implications of transferring mortgage objects without creditor consent and to examine the responsibility of notaries in drafting Sale and Purchase Binding Agreements and Powers of Attorney to Sell from the perspective of the principles of balance and good faith. Methods of the Research: This research employs a normative legal research method using statutory, conceptual, and case approaches. The legal materials consist of primary legal materials in the form of laws and regulations related to mortgage rights, secondary legal materials such as books and scholarly journals, and tertiary legal materials including legal dictionaries. Data collection was conducted through library research, which was then analyzed qualitatively using a descriptive-analytical method to obtain systematic conclusions. Findings of the Research: The results indicate that the transfer of mortgage objects without creditor consent does not eliminate the security right attached to the object due to the application of the droit de suite principle, thereby ensuring that creditors retain preferential rights and execution authority. Such actions constitute a breach of contract and violate the principles of good faith and balance. Furthermore, notaries are required to act carefully, honestly, and impartially in drafting legal documents. If a notary knows or should have known that the object is still encumbered by a mortgage, administrative, civil, and even criminal liability may arise. Thus, the mortgage law system in Indonesia provides strong legal protection for creditors, while notaries are required to uphold prudence to ensure legal certainty and fairness for all parties.